Non-Productive Time Reduction during Oil Wells Drilling Operations - Assi, Amel H. (Journal of Petroleum Research and Studies, 2022)
Often there is no well drilling without problems. The solution lies in managing and evaluating these problems and developing strategies to manage and scale them. Non-productive time (NPT) is one of the main causes of delayed drilling operations. Many events or possibilities can lead to a halt in drilling operations or a marginal decrease in the advancement of drilling, this is called (NPT). Reducing NPT has an important impact on the total expenditure, time and cost are considered one of the most important success factors in the oil industry. In other words, steps must be taken to investigate and eliminate loss of time, that is, unproductive time in the drilling rig in order to save time and cost and reduce wasted time. The data of six oil wells were approved for the purpose of the study, where it was noted that there are many factors affecting the NPT, which differ from one well to another. Its impact was limited to drilling rig, mud pump and equipment failure. There is also a difference between the planned program and what is actually happening on the ground, due to several reasons, including human errors during the implementation of the drilling program and others due to technical errors, Misuse of equipment, in addition to human errors related to the failure to implement the drilling program.